Analisis Usability Pada Implementasi Sistem Pengelolaan Keuangan Masjid Menggunakan USE Questionnaire - Fachruddin, Fachruddin; Pahlevi, Muhammad Riza; Ismail, Muhammad; Rasywir, Errissya; Pratama, Yovi (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
The financial management of mosques with the use of technology can make financial data more organized, filed neatly and transparently. Moreover, financial reports are data that must be accounted for in order to be trusted by the public. However, it is necessary to know how good a financial management system is. By using the USE Questionnaire we can find out that an application can still run in accordance with applicable business processes without changing the data flow and some rules and reports that have been running previously. The need to analyze usability testing on financial applications is to support automatic and computerized mosque financial management and is considered very good in user testing. This study resulted in an average rating for the "Usefulness" instrument, the "Ease of Use" instrument, the "Ease of Learning and Satisfaction" instrument, which scored well above 93%. The â€œUsefulnessâ€ instrument received an average of 99.00%, the â€œEase of Useâ€ instrument received an average of 94.55%, the â€œEase of Learning and Satisfactionâ€ instrument received an average of 93.82%. Thus it can be stated that the mosque financial application built for mosque management is able to meet good criteria in the rules of the USE Questionnaire method.